"We Only Speak English Here": English Dominance in Language Diverse, Immigrant After-School Programs. (January 2017) - Gast, Melanie Jones; Okamoto, Dina G.; Feldman, Valerie
Past research suggests that community after-school programs (ASPs) are crucial sites for culturally relevant programming for minority and immigrant youth; yet, we know little about how ASPs address language in their programming. Using an ethnographic fieldwork approach, we examine the goals and practices of ASP workers serving immigrant youth with diverse ethnic and language backgrounds in San Francisco, California. We find that, despite the best intentions regarding culturally relevant programming, ASP workers faced funding mandates, capacity issues, and increasingly diverse youth populations, and they adopted English-only policies or simply placed little priority on native-language usage. Ultimately, we observed competing processes related to English dominance: a lack of support for English language learners (ELLs) and bilingual youth, and the use of English as a bridge language across racial and ethnic lines. While staff sought to support and empower immigrant youth, ELL youth were often left on the sidelines and had limited opportunities to develop social capital in ASPs. Without reworking funding and institutional systems for language programming, English dominance may continue as a normalized method of practice in city youth programs.